Defining service quality in tramp shipping : conceptual model and empirical evidence - Tay, Wei Jun (2014)
Tramp shipping constitutes a prominent segment of the shipping market. As customers increasingly seek value from service providers for low price but yet high quality services, there is a pressing need to understand critically what construe the service quality for the tramp sector. In this respect, however, no prior research has been conducted for this market segment. This study recognises the gap in the existing maritime literature and aimed to propose and validate a service quality (SQ) model to address such a gap. The study employs a triangulation approach, utilising literature review, interviews and surveys to develop, refine and verify the SQ model proposed. Interviews were conducted with various parties in the tramp sector while a survey using a sample size of 343 tramp shippers and 254 tramp service providers was also conducted with tramp shippers and tramp service providers. It was revealed that the SQ model of six dimensions of Corporate Image, Customer Focus, Management, Outcomes, Personnel and Technical, and their 18 associated attributes could be used as a reliable tool to measure service quality in tramp shipping. This research contributes to fill the gap in the existing literature by introducing and validating a new SQ model specifically for tramp shipping. Meanwhile, the model can also be used by practitioners to receive their customers’ evaluation of their service quality as well as a benchmarking tool for continuous improvement. This study is, however, confined to a small-sized data collected in Singapore and to the bulk commodity context. Further studies on the practicality of the SQ model involving larger sample size and in other regions and for the general and specialized cargoes would be required to enhance its reliability.